Head-to-Head Comparison of the Expression Differences of NECTIN-4, TROP-2, and HER2 in Urothelial Carcinoma and Its Histologic Variants - Fan, Yu; Li, Qinhan; Shen, Qi; Liu, Zhifu; Zhang, Zhenan; Hu, Shuai; Yu, Wei; He, Zhisong; He, Qun; Zhang, Qian (Frontiers in Oncology, 2022)
Background： Antibody-drug conjugates (ADC), such as enfortumab vedotin (EV), Sacituzumab govitecan (SG) and RC-48, have shown outstanding response rates to local advanced or metastatic Urothelial carcinoma (UC). However, their corresponding targets expression characteristic in UC and its histologic variants were unknown. Methods： We detected the expression of NECTIN-4, TROP-2 and HER2, which are the corresponding targets of ADCs EV, SG and RC-48 in muscle invasive UC through immunohistochemistry. Results： 161 consecutive samples from 2017 to 2021 of muscle invasive UC and its histologic variants were obtained in Peking University First Hospital. Variant histology types included 72UC, 10 squamous carcinomas, 23 glandular carcinomas, 19 small cell carcinomas, 19 micropapillary variants and 18 nested variants. NECTIN-4 expression was found to be 57/72 (79.2%), 10/10 (100%), 15/23 (65.2%), 4/19 (21.1%), 15/19 (78.9%) and 16/18 (88.9%) in conventional UC, squamous carcinoma, glandular carcinoma, small cell carcinoma, micropapillary and nested variant, respectively, compared with 65/72 (90.3%), 8/10 (80.0%,), 13/23 (56.5%), 3/19 (15.8%), 16/19 (84.2%) and 15/18 (83.3%) of TROP-2, and 26/72 (36.1%), 0, 5/23 (21.7%), 6/19 (31.6%), 5/19 (26.3%) and 7/18 (38.9%) of HER2.